New UV‐Curable Anticorrosion Coatings from Vegetable Oils. Issue 6 (19th March 2021) - Noè, Camilla; Iannucci, Leonardo; Malburet, Samuel; Graillot, Alain; Sangermano, Marco; Grassini, Sabrina
Abstract: Bio‐based epoxy resins are attracting widespread interest in the field of polymer thermosets as environmentally friendly building block. In the present study, the feasibility of applying UV‐curable epoxidized vegetable oils (EVOs) as anti‐corrosion coating is investigated. Rheological characterization of EVOs is carried out, and their viscosity‐shear relationship is evaluated. The cationic UV‐curing of EVOs successfully gives rise to crosslinked materials with a wide range of thermo‐mechanical properties, evaluated by differential scanning calorimetric analysis and dynamic thermal mechanical analysis. A high epoxy‐group conversion, ranging from 93% to 99%, is always obtained. The thermal stability and surface properties of the bio‐based coatings, such as, pencil hardness, adhesion, solvent resistance, and contact angle, are analyzed. Moreover, the corrosion protection effectiveness of the coatings is characterized by potentiodynamic polarization and electrochemical impedance spectroscopy measurements. In addition, field emission scanning electron microscopy is used to assess the samples morphology after corrosion tests. Abstract : This paper presents a comprehensive characterization of the bio‐based thermosets obtained from three different epoxidized triglycerides; the specific application for anticorrosion coatings is investigated using electrochemical measurements. Results highlight the good corrosion protection behavior of the coatings, specifically for the formulation having the highest epoxy content; this can be correlated to the high cross‐linking density and higher glass transition temperature.